Analysis of technologies for the foamglass production - Pshinko, O. M.; Krasniuk, O. V.; Hrebennikov, V. M.; Shcherbak, A. S. (Science and Transport Progress, 2010)
The existing types of foamglass production technologies are considered in the article. Their advantages and demerits are shown.